Determinants of nesting success in Turtle doves (Streptopelia turtur) in a North-African agricultural area - (:unkn) unknown (My University, 2015)
Determining the effects of environmental factors on nesting success of migrant and breeding game birds is paramount especially in man-made environments. Using Poisson regression, we investigated the influence on the number of chicks fledged per nest (N = 207) of nest placement, proximity of cereal crops and water sources, taking into account possible phenological and spatial differences between the five studied orchards. The best model, selected by Akaike criterion, shows positive linear effects of distance from the nest to the trunk, to closest cereal crops and a quadratic effect of nest height (with an optimum at 1.6m). In Guelma’s orange groves, nest placement and proximity to cereal crops have a direct impact on the productivity of Turtle doves. Further researches on other tree species (fruit and forest ones) are necessary to: (i) assess their importance for breeding Turtle doves and (ii) determine the effect of environmental variables on the maintenance of the species.
Keywords: African Research